Ammonia as Green Fuel in Internal Combustion Engines: State-of-the-Art and Future Perspectives - Tornatore, Cinzia; Marchitto, Luca; Sabia, Pino; De Joannon, Mara (Frontiers in Mechanical Engineering, 2022)
Ammonia (NH3) is among the largest-volume chemicals produced and distributed in the world and is mainly known for its use as a fertilizer in the agricultural sector. In recent years, it has sparked interest in the possibility of working as a high-quality energy carrier and as a carbon free fuel in internal combustion engines (ICEs). This review paper aims to provide an overview of the research on the use of green ammonia as an alternative fuel for ICEs with a look to the future on possible applications and practical solutions to related problems. First of all, ammonia production process is discussed. Present ammonia production is not a "green" process, the synthesis occurs starting from gaseous hydrogen currently produced from hydrocarbons. Some ways to produce green ammonia are reviewed and discussed. Then, the chemical and physical properties of ammonia as a fuel are described and explained in order to identify the main pros and cons in its use in combustion systems. Then the most viable solutions for fueling internal combustion engines with ammonia are discussed. When using pure ammonia high boost pressure and compression ratio are required to compensate the low ammonia flame speed. In spark ignition engines adding hydrogen to ammonia helps speeding up the flame front propagation and stabilizing the combustion. In Compression Ignition engines ammonia can be successfully used in dual-fuel mode with diesel. On the other hand, NOx increase and unburned NH3 at the exhaust requires the installation of apposite aftertreatment systems. Therefore, the use of ammonia seems to be more practicable for marine or stationary engine application where space constrains are not a problem. In conclusion this review points out that ammonia has excellent potential to play a significant role as a sustainable fuel for the future in both retrofitted and new engines. However, significant further research and development activities are required before being able to consider large-scale industrial production of green ammonia. Moreover, uncertainties remain about ammonia safe and effective use and some technical issues need to be addressed to overcome poor combustion properties for utilization as a direct substitute of standard fuels.